Comparison of qSOFA, MEDS, and APACHE II Scores in Early Identification of Sepsis for Patients with 28 days Mortality and ICU Admission: A cross-sectional Study - PD Shiv Ranjit; Akilan Elangovan; TV Ramakrishnan; Tamilanbu Panneerselvam; J Janifer Jasmine (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Sepsis is a life-threatening infection that results in organ dysfunction due to an increased pathogen load, necessitating urgent intervention. There is a gap in clinicians’ ability to identify septic patients at high-risk with poor outcomes, highlighting the need for validated predictive scores for early intervention, favourable outcomes, and prompt recovery. Aim: To validate the predictive capacity of the Sequential Organ Failure Assessment (qSOFA), Mortality in Emergency Department Sepsis (MEDS), and Acute Physiology and Chronic Health Evaluation (APACHE 2) scores in patients with 28-day mortality and in Intensive Care Unit (ICU) patients due to sepsis. Materials and Methods: This cross-sectional study was conducted on 150 septic patients at the Department of Emergency Medicine, Sri Ramachandra Institute of Higher Education and Research in Chennai, India, between June and December 2022. Parameters assessed included Respiratory Rate (RR), Systolic Blood Pressure (SBP), Mean Arterial Pressure (MAP), temperature, White Blood Cell (WBC) count, platelet count, bilirubin, and creatinine. Descriptive analysis of age, gender, source, RR, GCS, SBP, qSOFA, MEDS, APACHE 2 in 28-day mortality, and ICU patients. Positive correlation and good predictivity of predictive scores (qSOFA, MEDS, APACHE 2) were analysed using Spearman’s Rank Correlation Coefficient (SRCCRs) statistical test in 28-day mortality and ICU patients. Results: A total of 150 septic patients (male: female-93:57) with an average age of 57.07±14.4 years were included. Urosepsis was the most common (n=51), followed by respiratory sepsis (n=48). Of these, 96 patients were admitted to the ICU, and 54 patients experienced 28-day mortality. The average and median values of RR were 27.1±7.64 breaths/minute (b/m) and 26 b/m, respectively. SBP values were 106.13±30.47 mmHg and 110 mmHg, respectively. Diastolic Blood Pressure (DBP) values were 66±16.51 mmHg and 60 mmHg, respectively. The average and median values of GCS were 12.75±3.92 and 15, respectively. The average for qSOFA was 29.1±0.025, with a median of 28; for MEDS, the average was 7.99±5.89, with a median of 7; and for APACHE 2, the average was 16.74±9.64, with a median of 15. Spearman’s Rank Correlation Coefficient (SRCCRs) demonstrated a strong positive correlation and good predictive validity between qSOFA, MEDS, and APACHE 2 scores in 28-day mortality and ICU patients (<0.001). Receiver Operating Characteristic Curve (ROC) analysis indicated good predictive validity for qSOFA in 28-day mortality and ICU patients. Conclusion: qSOFA exhibited a positive correlation and good predictive validity compared to MEDS and APACHE 2 in both 28-day mortality and ICU patients (<0.001). This study highlights the utility and applicability of qSOFA at the bedside for initial triage, as it can be quickly employed with minimal information.